AKIBAT HUKUM PEMBATALAN AKTA JUAL BELI TANAH MELALUI PUTUSAN PENGADILAN NEGERI TERHADAP KEPEMILIKAN HAK ATAS TANAH - Agustin, Elvan; Fahmi; Harahap, Irawan (Collegium Studiosum Journal, 2025)
The Cancellation of Land Sale and Purchase Deeds through Court Decisions Has Complex Implications. It not only alters the legal status of land ownership but also affects the civil rights of the parties involved, the legal responsibilities of the Land Deed Official (PPAT), and administrative arrangements at the National Land Agency (BPN). Therefore, the cancellation process must be carried out carefully and based on strong evidence to avoid creating new legal uncertainties in society. The method used is normative legal research. Based on the research findings, Legal Protection for Good Faith Buyers emphasizes that every land sale and purchase transaction must comply with applicable legal provisions. A good faith buyer—one who purchases land honestly and without knowledge of legal defects in the transaction—is entitled to legal protection. If a land sale and purchase deed is cancelled by a court decision, the good faith buyer must be protected through compensation or a refund to ensure their rights are not neglected. The Legal Consequences of the Cancellation of a Land Sale and Purchase Deed through a Court Decision impact the ownership status of the land. Such cancellation causes the land rights to revert to the seller, and the buyer can no longer claim ownership. In this case, a refund or compensation becomes an essential step to restore the good faith buyer’s position. Additionally, the land administration process must be updated to reflect the new status of the land in accordance with the court's decision.